A Randomized, Controlled, Multicenter Study of Juvéderm Voluma for Enhancement of Malar Volume in Chinese Subjects. Issue 6 (June 2017) - Li, Dong; Wang, Xiaojun; Wu, Yan; Sun, Jiaming; Li, Qin; Guo, Shuzhong; Jia, Yi; Murphy, Diane K.
Abstract : Background: Hyaluronic acid gels are used to restore volume to the midface, but there are few data published on this use in Asian subjects. Methods: This study evaluated the safety and effectiveness in Chinese subjects of Juvéderm Voluma, a 20-mg/ml hyaluronic acid gel formulated for midface volumizing. This prospective, multicenter study randomized 119 subjects aged 18 years or older to a treatment group and 27 subjects to a no-treatment control group. The primary effectiveness endpoint was the objectively measured magnitude of change from baseline in volume of the midface area (right and left combined) calculated by digital analysis at month 6 using three-dimensional images for all subjects in both groups. Effectiveness was protocol-defined as a mean change for the treatment group that was significantly greater than that for the control group at month 6 using a one-side two-group t test performed at the 5 percent level. Results: With a median volume of 2 ml of Voluma injected, the primary effectiveness endpoint was met, with the mean change from baseline to 6 months in malar volume for the treatment group (1.83 ml) being significantly greater than that for the control group (0.11 ml; p < 0.001). The secondary effectiveness endpoints of responder rate (malar volumization rated improved or much improved) using the Global Aesthetic Improvement Scale as assessed at month 6 by the investigator and by the subject were 98.2 and 93.8 percent, respectively. The most common treatment-related adverse events were mild injection-site swelling and bruising. Conclusion: Juvéderm Voluma is effective and well tolerated for midface augmentation in Chinese subjects. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.